Treatment of venous thromboembolism - Rizzatti, Edgar Gil; Franco, Rendrik F. (Medicina (Ribeirao Preto), 2001)
Deep vein thrombosis (DVT) is defined as an episode of thrombosis involving deep veins, usually of the lower limbs. DVT is frequently accompanied by pulmonary embolism (PE). Venous thromboembolism (VTE) is the generic term commonly used to refer to both clinical conditions indistinctly. In this paper, we present a brief review of current concepts in the treatment of VTE. Use of unfractionated and low molecular weight heparin is approached, and special attention is given to its transition to long term use of oral anticoagulants. In addition, specific therapeutic measures in special clinical conditions and in the supportive management of patients with VTE are also discussed.